Analisis Tax Awareness Dalam Upaya Meningkatkan Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak Pratama Bekasi Barat - Nunung Latofah; Dwikora Harjo (Jurnal Pajak Vokasi (JUPASI), 2020)
The phenomenon in this study is the low awareness of taxpayers in carrying out their obligations to pay taxes due to public ignorance of the concrete form of the benefits of money they pay for taxes and the low level of trust of taxpayers which raises the perception that the taxes they pay must be misused. The purpose of this study was to determine the tax awareness in an effort to increase taxpayer compliance at the West Bekasi Tax Office for the period 2017-2019, the obstacles found in the field, and the efforts made by West Bekasi Tax Office to overcome them. This research is a descriptive study using a qualitative approach. The collected data were analyzed using qualitative data analysis methods. The research location was the West Bekasi Primary Tax Office. The results of this study indicate that the steps to increase tax awareness among taxpayers registered at the West Bekasi Primary Tax Office during the 2017-2019 period was not successful. This can be seen from the realization of the 2019 tax revenue which did not reach the target (97.05%) even though that year the tax revenue target was lowered from the previous year. Likewise, while taxpayer compliance in paying certain KJS (Deposit Type Code) increased in 2017-2019, tax revenue had still not reached the predetermined target every year